2016
DOI: 10.1021/acs.nanolett.5b04709
|View full text |Cite
|
Sign up to set email alerts
|

Deterministic Integration of Single Photon Sources in Silicon Based Photonic Circuits

Abstract: A major step toward fully integrated quantum optics is the deterministic incorporation of high quality single photon sources in on-chip optical circuits. We show a novel hybrid approach in which preselected III-V single quantum dots in nanowires are transferred and integrated in silicon based photonic circuits. The quantum emitters maintain their high optical quality after integration as verified by measuring a low multiphoton probability of 0.07 ± 0.07 and emission line width as narrow as 3.45 ± 0.48 GHz. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
161
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(167 citation statements)
references
References 46 publications
3
161
0
Order By: Relevance
“…Such wavelength converters enable long distance quantum state transfer from flying qubit to a stationary qubit or vice versa, and entanglement distribution between two remote matter qubits in long‐distance quantum networks . The high conversion efficiencies that are achievable in LNOI, makes this platform very attractive for such wavelength down conversion schemes and the integration of quantum dots in such waveguides seems also feasible …”
Section: Emerging and Potential Future Applicationsmentioning
confidence: 99%
“…Such wavelength converters enable long distance quantum state transfer from flying qubit to a stationary qubit or vice versa, and entanglement distribution between two remote matter qubits in long‐distance quantum networks . The high conversion efficiencies that are achievable in LNOI, makes this platform very attractive for such wavelength down conversion schemes and the integration of quantum dots in such waveguides seems also feasible …”
Section: Emerging and Potential Future Applicationsmentioning
confidence: 99%
“…Additionally, Murray et al [175] demonstrated orthogonal bonding of a GaAs chip containing QDs and a silicon photonic chip with single-qubit circuitry. Probe-based manipulation has allowed integrating QDs into SiN waveguides [176] and onto MEMS tuners [168] (see Figure 6b), as well as positioning nanodiamond-based NV centers into photonic crystal structures [177] and plasmonic waveguides [178]. Diamond microwaveguides and PCCs containing single NV centers have been hybridized onto silicon chips [179,180], promising high quality hybrid quantum memories and single-photon sources (especially in the case of SiV centers).…”
Section: Beyond Single-platform Approachesmentioning
confidence: 99%
“…An alternative scheme is to use quantum emitters with naturally sub-Poissonian photon statistics within a waveguide circuit made of the emitter's host material. [17][18][19][20] It is also possible to evanescently couple the emitter to a low-loss PIC [21][22][23] and these schemes have verified the emission of single photons. However, for realising large scale and compact circuits, it will be necessary to integrate multiple sources of indistinguishable photons on the chip, as we demonstrate here.…”
mentioning
confidence: 99%